Impaired deoxyribonuclease I activity in patients with inflammatory bowel diseases - Malíčková, Karin; Duricová, Dana; Bortlík, Martin; Hrušková, Zdenka; Svobodová, Barbora; Machková, Naděžda; Komárek, Viktor; Fučíková, Terezie; Janatková, Ivana; Zima, Tomáš; Lukáš, Milan (Autoimmune diseases, 2011)
Background and Aims. Deoxyribonuclease I (DNaseI) is an endonuclease that facilitates chromatin breakdown and promotes susceptibility to autoimmune disorders. The aim of current study was to investigate serum DNase I activity in patients with inflammatory bowel diseases (IBD). Patients and Methods. A cohort of 110 IBD patients was evaluated, aged 35 ± 12 years, 77 with Crohn's disease (CD) and 33 with ulcerative colitis (UC). 50 SLE patients and 50 healthy blood donors were examined as control groups. Results. DNase I activity in IBD patients was significantly lower than in healthy individuals, but higher than in SLE patients (P < .0001). Patients with UC showed higher DNase I activity than CD patients, P = .21. DNase I activity in female patients with IBD was significantly lower than in males, P = .024; however, no differences in DNase I activity were found in relation to gender in healthy individuals. DNase I activity has shown a strong negative correlation with the serum concentration of anti-nucleosomal antibodies in the autoimmune (SLE + IBD) cohort, as well as in the separate IBD cohort. Conclusions. Reduced serum DNase I activity probably has pathogenetic consequences in IBD. Induction of autoantibodies towards nucleosomes could be a reflection of impaired DNase I activity.